Chemical composition of the Essential oil from stems, leaves and flowers of Salvia verticillate L. - Navid Salehi (Journal of Chemistry Letters)
The water- distilled essential oil from stems, leaves and flowers of salvia verticillate L.Were analyzed by GC and GC/MS. the major component of the flowers oil were β-gurjunene(14.56%),δ-Elemene(9.01%), and 1,8- cineol(7.36%).the main component inThe leaves oil were 1,8-cineol(20.14%), α-pinene(16.3%), δ-Elemene(10.38%), β-pinene(9.13%) and β-gurjunene(5.36%).The main constituent of the oil obtained from stems of the plant were 1,8-cineol(35.60%)and β-pinen(6.87%) .